Kesiapan, Gaya Belajar dan Keaktifan Siswa Pada Pembelajaran Pendidikan Agama Islam di SMPN Bangkinang Kota - Afandi, Muslim; Zuraidah, Zuraidah (Belajea: Jurnal Pendidikan Islam, 2020)
This study aims to find out whether or not there is a significant influence of readiness and learning styles on students’ learning activeness in Islamic education learning at state elementary schools in the district of Bangkinang Kota. This is a correlational study employing a quantitative approach. The study population amounted to 1529 students, and the samples were 317 students. The sampling deployed the Slovin formula with an error degree of 5%. The sampling technique used proportionate stratified random sampling. Data collection techniques used questionnaires, observation, and documentation. The data analysis technique used multiple regression. The instruments used in this study had met the criteria of validity and reliability (r1 = 0.214 and r2 = 0.254). The results showed that there was a significant influence of learning readiness on students’ learning activeness; there was a significant influence of learning styles on students’ learning activeness; and there was a significant influence of learning readiness and learning styles on students’ learning activeness.